2011
DOI: 10.1080/13504851.2010.511990
|View full text |Cite
|
Sign up to set email alerts
|

Wage differentials between East and West Germany: are they related to the location or to the people?

Abstract: Despite rapid economic integration and massive help from the Federal Government, large wage differences between East and West Germany still persist. We ask whether those differences are related to disadvantageous locational conditions in East Germany or could be found in the characteristics of the people living there. This article analyses income adjustment of East-West migrants based on the German Socio-Economic Panel (GSOEP), 1990-2008. Because migrants earned their income in both East and West Germany, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
1
24
1
Order By: Relevance
“…To allow the association between nutrition-related behaviours and maternal labour force participation to differ across regions, we also include an interaction term for region and maternal labour force participation. This interaction would account for a differential response to maternal labour force participation which could come about from persistent differentials in wages post reunification (26) .…”
Section: Independent Variablesmentioning
confidence: 99%
“…To allow the association between nutrition-related behaviours and maternal labour force participation to differ across regions, we also include an interaction term for region and maternal labour force participation. This interaction would account for a differential response to maternal labour force participation which could come about from persistent differentials in wages post reunification (26) .…”
Section: Independent Variablesmentioning
confidence: 99%
“…This effect should show up particularly for older cohorts of workers in eastern Germany. This will be investigated in the next subsections and supplements former research on a similar topic (Orlowski/Riphahn 2009, Smolny/Kirbach 2011.…”
Section: Direct Labour Market Consequencesmentioning
confidence: 99%
“…A quarter of a century after unification, this is rather astounding, particularly because it has been shown that the characteristics of people in East Germany are very similar to those of people in the West. Smolny and Kirbach (2011) examined migrants between East and West and ascertained that wage differences could not be attributed to the characteristics of workers. The question is then, what locational conditions and characteristics of firms produce these differences, if they cannot be related to workers.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the gender gap is known to differ markedly in Western and Eastern Germany: while mean wages are generally lower in Easter Germany, women face a much smaller penalty relative to men than in Western Germany (see, e.g., Hunt, 2002;Smolny and Kirbach, 2011;Kohn and Antonczyk, 2013). Smolny and Kirbach (2011) observe that the gender wage gap is one of the few statistics for which there is no convergence to Western levels in the period 1990-2008. At the same time, Germany recently experienced an increase in overall wage inequality; see, e.g., Dustmann et al (2009);Fuchs-Schündeln et al (2010); Card et al (2013).…”
mentioning
confidence: 99%
“…The size of the gender gap is known to differ markedly in Western and Eastern Germany: while mean wages are generally lower in Easter Germany, women face a much smaller penalty relative to men than in Western Germany (see, e.g., Hunt, 2002;Smolny and Kirbach, 2011;Kohn and Antonczyk, 2013). Smolny and Kirbach (2011) observe that the gender wage gap is one of the few statistics for which there is no convergence to Western levels in the period 1990-2008. At the same time, Germany recently experienced an increase in overall wage inequality; see, e.g., Dustmann et al (2009);Fuchs-Schündeln et al (2010); Card et al (2013). According to Al-Farhan's (2010b) analysis of the German Socio-Economic Panel (SOEP) data, the wage distribution in Germany appeared to stabilize at historically high levels of inequality in the recent ten years, while Antonczyk et al (2010Antonczyk et al ( , 2011 still find increasing wage inequality between 2001 and 2006 using Structure of Earnings data.…”
mentioning
confidence: 99%